2012
DOI: 10.1364/ol.37.001331
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow power continuous-wave frequency conversion in hydrogenated amorphous silicon waveguides

Abstract: We demonstrate wavelength conversion through nonlinear parametric processes in hydrogenated amorphous silicon (a-Si:H) with maximum conversion efficiency of -13 dB at telecommunication data rates (10 GHz) using only 15 mW of pump peak power. Conversion bandwidths as large as 150 nm (20 THz) are measured in continuous-wave regime at telecommunication wavelengths. The nonlinear refractive index of the material is determined by four-wave mixing (FWM) to be n(2)=7.43×10(-13) cm(2)/W, approximately an order of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 18 publications
3
54
0
Order By: Relevance
“…Although initial measurements yielded a FOM no better than c-Si (~0.5) [120,121], more recent results have shown FOMs ranging from 1 [122] to as high as 2 [123,124], allowing very high parametric gain (+26dB) over the C-band [125]. While a key problem for this material has been a lack of stability [126], very recently a-Si nanowires were demonstrated [127] that displayed a combination of high FOM of 5, high n 2 (3-4 times that of crystalline silicon) and good material stability at telecom wavelengths.…”
Section: Future Challenges Opportunitiesmentioning
confidence: 92%
“…Although initial measurements yielded a FOM no better than c-Si (~0.5) [120,121], more recent results have shown FOMs ranging from 1 [122] to as high as 2 [123,124], allowing very high parametric gain (+26dB) over the C-band [125]. While a key problem for this material has been a lack of stability [126], very recently a-Si nanowires were demonstrated [127] that displayed a combination of high FOM of 5, high n 2 (3-4 times that of crystalline silicon) and good material stability at telecom wavelengths.…”
Section: Future Challenges Opportunitiesmentioning
confidence: 92%
“…Furthermore, it is interesting to note that in a set of experiments involving 150 fs pulses to generate a supercontinuum at telecom wavelengths [45], no degradation could be observed. However, it also needs to be emphasized that other groups have demonstrated aSi:H waveguides, which are chemically stable at telecom wavelengths [36,37]. These groups have shown a multitude of demonstrations of all-optical signal processing experiments in a-Si:H waveguides [36] and even as a source for photon pair generation [46,47].…”
Section: Hydrogenated Amorphous Siliconmentioning
confidence: 99%
“…However, it also needs to be emphasized that other groups have demonstrated aSi:H waveguides, which are chemically stable at telecom wavelengths [36,37]. These groups have shown a multitude of demonstrations of all-optical signal processing experiments in a-Si:H waveguides [36] and even as a source for photon pair generation [46,47]. Lastly, by investigating the time-dependent response of hydrogenated amorphous silicon waveguides, it has been observed that the Kerr-like response is far from instantaneous [48].…”
Section: Hydrogenated Amorphous Siliconmentioning
confidence: 99%
“…However the relatively low optical confinement that could be achieved in such waveguides strongly reduces the value of the Reγ necessitating the use of relatively long waveguides in order to achieve all-optical processing by means of nonlinear effects [7]. Recently amorphous silicon (a-Si) waveguides emerged as a viable alternative to crystalline Silicon (c-Si), showing an increased nonlinear coefficient alongside a reduced TPAfactor [8], [9], [10]. Furthermore, a-Si layers can be grown at temperatures compatible with the back-end line, improving the CMOS material compatibility.…”
Section: Introductionmentioning
confidence: 99%